Keeping it 100: Social media and self-presentation in college football recruiting - Bigsby, K. G.; Ohlmann, J. W.; Zhao, K. (Big data, 2019)
Social media provides a platform for individuals to craft personal brands and influence their perception by others, including potential employers. Yet there remains a need for more research investigating the relationship between individuals' online identities and offline outcomes. This study focuses on the context of college football recruiting, specifically on the relationship between recruits' Twitter activities and coaches' scholarship offer decisions. Based on impression management theory, we analyze content posted by recruits and apply machine learning to identify instances of self-promotion and ingratiation in 5.5 million tweets. Using negative binomial regression, we discover that an athlete's level of engagement on Twitter is a positive and significant predictor of the number of offers. Also, both self-promotion and ingratiation are positively related to attracting new offers. Our results highlight the growing importance of social media as a recruiting tool and suggest that recruits' online self-presentation may have significant offline impacts. This research can benefit athletes and coaches by informing communication strategies during recruitment, and may also yield insight into the consequences of online impression management in other types of recruitment beyond sports.